ANALISIS PENERIMAAN PAJAK DAERAH DAN HASIL PENGELOLAAN KEKAYAAN DAERAH YANG DIPISAHKAN TERHADAP PENDAPATAN ASLI DAERAH PADA MASA PANDEMI, TRANSISI, DAN PASCA-PANDEMI COVID-19 (Studi pada Kabupaten dan Kota di Provinsi Jawa Tengah Tahun 2021–2023) - Poa Yosia Purnomo; Herry Laksito (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the effect of local tax revenue and revenue from separated regional asset management on Local Own-Source Revenue (PAD) during the COVID-19 pandemic, transition, and post-pandemic periods. The research covers 35 regencies and municipalities in Central Java for 2021–2023 using a quantitative approach with secondary data from BPK Audit Reports and BPS publications. The analysis applies panel data regression, preceded by descriptive statistics and model selection through the Chow, Hausman, and Lagrange Multiplier tests. The results show that local tax revenue has a positive and significant effect on PAD, while revenue from separated regional asset management has no significant impact. These findings indicate that although the performance of Region-Owned Enterprises (BUMD) improved in the post-pandemic period, their contribution to PAD remains limited compared to local taxes. The study also reveals differences in PAD dynamics across the pandemic, transition, and post-pandemic periods, reflecting variations in regional fiscal adaptability.